Unbuilding from the inside: leadership and democratisation in South Africa and South Korea - O'Brien, Thomas (Cranfield University, 2016)
Leaders have an important role in initiating and shaping the democratisation process. Although formal and informal structures within the political system constrain decisions leaders possess a degree of agency. This paper examines the actions of F.W. de Klerk (South Africa) and Roh Tae Woo (South Korea) in initiating processes that eventually led to the consolidation of democratic political systems. The differences in the domestic context raise questions about the degree to which they introduced change using similar approaches or whether their actions were predominantly shaped the environment. The aims of the paper are to: (1) identify the array of opportunities and threats faced by the two leaders; and (2) determine the effect of regime form in shaping these structural factors. Drawing on previous work on the role of leadership in democratisation, the analysis focuses on four factors: authority, institutions, opposition and continuity. To assess decisions made in the distinct political contexts the paper examines how the respective structural configuration (one-party and military) was managed.